Evaluating Managerial Supervision Practices for Teacher Performance Enhancement: Evidence from an Islamic Secondary School in Indonesia - Reizahra Diannisa; Gustianto Nur Hafis; Anisa Siti Hodijah; Sohiron Sohiron; Afriza Afriza; Hartono Hartono; Mardianto Mardianto; Saputra Hadi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study aims to analyze and evaluate the implementation of managerial supervision conducted by a madrasah principal, with particular attention to how supervision is planned, implemented, monitored, and evaluated to support teacher and administrative staff performance. A qualitative case study approach was employed. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that managerial supervision was implemented through four interconnected stages: systematic planning, classroom observations and individual guidance during implementation, continuous monitoring of teacher performance, and evaluation to identify areas for improvement. The study also found that effective managerial supervision was supported by visionary leadership, constructive communication between the principal and teachers, and institutional collaboration. However, its implementation was constrained by limited time allocation and available resources, which affected the consistency and scope of supervisory activities. These findings suggest that strengthening principals’ managerial and supervisory competencies through continuous professional development, alongside institutional support to address resource constraints, may enhance the effectiveness of managerial supervision and contribute to continuous school quality improvement.